ABU AL-HASAN ‘AMIRI: TOKOH MUSLIM PERBANDINGAN AGAMA ABAD KE-10 - Ashani, sholahuddin (UIN Sumatera Utara Medan, 2018)
This article discusses the study of Abu al-Hasan al-'Amri's thought regarding the comparative study of religion that developed during the Islamic period of the 10th century. The discussion is done by using phenomenology and verstehen approach which aims to reveal his thoughts without interfering with subjective interests. Amiri's thoughts contained in his books provide a clear exposure to the form of religious studies cultivated by Islamic thinkers of the 10th century. The most prominent character in the study of religious comparison among Islamic intellectuals at that time was more to show and prove the advantages of Islam among other religions. Expertise 'Amiri in the field of philosophy, theology and religious studies presents the exposure of Islam better than other religions.